APPLIED LINGUISTICS: TRIADIC SIGN MODELS IN PERSUASION METHODS OF NIVEA MEN’S PRODUCT PACKAGING - Mahendra, Alvin Gilbran; Nurulaen, Yuyun; Sakinah, R. Myrna Nur (Esteem Journal of English Education Study Programme, 2025)
This study aims to analyze the use of signs on Nivea Men product packaging, focusing on their interpretation and effectiveness in delivering persuasive messages. Employing Charles Sanders Peirce’s Triadic Relation Theory, a qualitative method was used to examine product categories and their connection to everyday experiences. Data were collected through observation and documentation from Nivea Men’s official website, then analyzed using triadic theory and persuasion methods. The results reveal that signs significantly influence consumer interpretation and the persuasive value of products, although some signs do not fully align with their intended meanings. This study highlights the importance of designing clear and purposeful signs to enhance advertising strategies and consumer understanding. Future research should focus on refining semiotic and persuasion techniques to align signs more effectively with product identity and market needs.